Prairie ghost : pronghorn and human interaction in early America - McCabe, Richard E. (University Press of Colorado, 2010)
In this lavishly illustrated volume, Richard E. McCabe, Bart W. O'Gara and Henry M. Reeves explore the fascinating relationship of pronghorn with people in early America, from prehistoric evidence through the Battle of Little Bighorn in 1876. The only one of fourteen pronghorn-like genera to survive the great extinction brought on by human migration into North America, the pronghorn has a long and unique history of interaction with humans on the continent, a history that until now has largely remained unwritten. With nearly 150 black-and-white photographs, 16 pages of color illustrations, plu.